Juvenile delinquency in India : an etiological analysis - Sarkar, Chandana, 1953- (Delhi : Daya Pub. House, 1987)
With reference to West Bengal, India
Includes index
Bibliography: p. [337]-346
Keywords: Juvenile delinquency -- India -- West Bengal; Juvenile delinquency